2023
DOI: 10.1021/acs.inorgchem.2c04384
|View full text |Cite
|
Sign up to set email alerts
|

Selective Complexation and Separation of Uranium(VI) from Thorium(IV) with New Tetradentate N,O-Hybrid Diamide Ligands: Synthesis, Extraction, Spectroscopy, and Crystallographic Studies

Abstract: An unmet challenge in the thorium-uranium fuel cycle is the efficient separation of uranium from thorium. Herein, two new tetradentate N,O-hybrid ligands, N,N′-diethyl-N,N′-di-p-tolyl-2,2′-bipyridine-6,6′-dicarboxamide (Et-Tol-BPDA) and N,N′-diethyl-N,N′-di-p-tolyl-2,2′-bipyrimidine-4,4′-dicarboxamide (Et-Tol-BPymDA), comprising a bipyridine or bipyrimidine core and amide moieties were designed and synthesized for selectively complexing and separating U(VI) from Th(IV). The high U(VI)/ Th(IV) extraction select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…This anti-anti-anti conformation was observed for similar bipyridine based diamides. 44,85 In ref. 38 it was shown that the conformation for a similar bipyridyl ligand in solution and crystal is comparable.…”
Section: Crystal Datamentioning
confidence: 99%
“…This anti-anti-anti conformation was observed for similar bipyridine based diamides. 44,85 In ref. 38 it was shown that the conformation for a similar bipyridyl ligand in solution and crystal is comparable.…”
Section: Crystal Datamentioning
confidence: 99%
“…Nuclear energy is deemed as a greener and safer energy source than traditional fossil fuels, with almost negligible CO 2 emission but much higher energy output than other emerging options including solar, wind, tidal, etc . 1,2 Nuclear power has contributed approximately 11% of the total electricity in the world, and the proportion is still increasing fast with the explosively rapid development of contemporary industries and the global energy shortage. 3 However, the associated radioactive nuclear wastes have brought severe threats to the environmental system, which are of high priority to deal with for sustainable development and public acceptance of nuclear energy.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of trivalent actinides and lanthanides is one of the most difficult tasks in separation chemistry due to their similar chemical properties. Although much progress has been made concerning the development of extractants, the liquid–liquid extraction process has certain drawbacks, such as excess utilization of volatile organic compound (VOC)-based solvents, secondary waste accumulation, emulsion formation between phases, and multistage extraction processes, which will affect the economic performance of the process in large-scale practical applications. Alternatively, solid-phase extraction technique has been considered as a relatively “green” separation method with high separation efficiency due to the possibility of column mode operation and easy scale-up options.…”
Section: Introductionmentioning
confidence: 99%